Ammonia removal during leach-bed acidification leads to optimized organic acid production from chicken manure. (February 2020) - Ramm, Patrice; Abendroth, Christian; Latorre-Pérez, Adriel; Herrmann, Christiane; Sebök, Stefan; Geißler, Anne; Vilanova, Cristina; Porcar, Manuel; Dornack, Christina; Bürger, Christoph; Schwarz, Hannah; Luschnig, Olaf
Abstract: This work demonstrates the suitability of nitrogen removal during anaerobic acidification in batch configuration for a more efficient pre-treatment of chicken manure prior to anaerobic digestion. High loading rates corresponding to a total nitrogen input between 6.3 and 9.5 g L −1 allowed successful suppression of methanogenic archaea. To eliminate nitrogen, NH3 -stripping and MAP (magnesium ammonium phosphate hexahydrate) precipitation were compared. In spite of decreased cell quantities detected using qPCR, removal of nitrogen caused an increase in volatile fatty acid (VFA) formation from 13 to 19%. The highest nitrogen removal during acidification (up to 29%) was achieved with three consecutives MAP precipitation steps, however, conductivity values were affected too, reaching 53.3 and 53.1 mS cm −1 after the three consecutive MAP precipitations. Additionally, MAP-precipitation reduced the concentration of important trace elements and 16S-rRNA amplicon sequencing revealed an altered taxonomic pattern, in which especially the bacterial families Marinilabiliaceae, Bacteroidales UCG-001, M2PB4-65 termite group and Idiomarinaceae were impaired. However, in spite of these inhibitory effects, nitrogen removal proved able to prevent unwanted methanogenesis and to enhance the yield of VFAs, and this strategy thus holds great potential for the optimized production of biogas in a two-phase system. Highlights: Combining acidification and N-elimination enhances organic acid production. NH3 -stripping and MAP-precipitation reduce N-concentration. NH3 -stripping and MAP-precipitation reduce methane formation during acidification. Microbial shifts due to NH3 -stripping or MAP-precipitation were characterized. NH3 -stripping and MAP-precipitation lead to precipitation of trace elements.